Draw 50 famous caricatures - Ames, Lee J.; Drucker, Mort. (New York : Doubleday, 1990)
Step-by-step instructions for drawing caricatures of fifty famous people.
Booklist.
6.1
5-8
Keywords: Cartooning -- Technique -- Juvenile literature; Cartooning -- Technique; Portrait drawing -- Technique; Drawing -- Technique; Portrait drawing -- Technique; Drawing -- Technique; Cartoons and caricatures -- Technique; Cartooning -- Technique; Portrait drawing -- Technique; Drawing -- Technique